Action through Partnerships : The Pan-Caribbean Partnership Against HIV/AIDS (PANCAP) - Mulusa, Mary; Carpio, Carmen (World Bank, Washington, DC, 2012)
The Pan-Caribbean Partnership against HIV/AIDS (PANCAP) was designated an 'international best practice' by the Joint United Nations Program on HIV/AIDS (UNAIDS). A case study on the Pan-Caribbean Partnership against HIV/AIDS (PANCAP) in December, 2004. The Caribbean region is second only to Sub-Saharan Africa in HIV prevalence with an estimated adult HIV prevalence rate of 2.3 percent in 2003. Approximately 430,000 adults and 23,000 children are living with HIV in the region. HIV/ AIDS are the leading cause of death among adults in the age group 15-44 years. The epidemic is not just a health problem, but a developmental and economic problem as it affects the most productive human resources and redirects efforts from productive activities to HIV/AIDS treatment and care. A number of lessons emerge from PANCAP's experience. The building of the partnership was regionally led and owned. En Breve is proud to present the HIV/AIDS series which will run from January until June of 2005. The series looks to raise awareness on how HIV/AIDS directly affects the overall development of the region focusing on the Caribbean.